2017
DOI: 10.12659/msm.902530
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effect of Sodium Glucose Co-Transporter 2 Inhibitor Dapagliflozin on Renal Cell Carcinoma

Abstract: BackgroundPatients with type 2 diabetes mellitus (T2DM) have a high incidence of renal cell carcinoma (RCC) and high sodium glucose co-transporters 2 (SGLT2) expressions. The purpose of this study was to evaluate the anticancer activity of dapagliflozin as an SGLT2 inhibitor on RCC cell lines in vitro and in vivo.Material/MethodsqRT-PCR and Western blot were used to detect SGLT2 expression on different human renal cells. Then, flow cytometry and immunofluorescence were used to investigate the effects of dapagl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 19 publications
3
51
0
5
Order By: Relevance
“…2 A recent study reported that dapagliflozin, an SGLT2 inhibitor, reduces the viability of renal cell carcinoma cell lines, thus regulating the cell cycle and apoptosis in vitro and in vivo. 3 In liver cancer cells, canaglifrozin inhibits cell growth by not only inhibiting glucose uptake but also by affecting intratumor angiogenesis. 5 It is possible that ipragliflozin affects both glucose uptake and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 A recent study reported that dapagliflozin, an SGLT2 inhibitor, reduces the viability of renal cell carcinoma cell lines, thus regulating the cell cycle and apoptosis in vitro and in vivo. 3 In liver cancer cells, canaglifrozin inhibits cell growth by not only inhibiting glucose uptake but also by affecting intratumor angiogenesis. 5 It is possible that ipragliflozin affects both glucose uptake and tumor angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…SGLT2 inhibitors are a new class of therapeutic agents indicating type 2 diabetes mellitus, reducing glucose reabsorption in the renal proximal tubule, and plasma glucose levels . A recent study reported that SGLT2 inhibitors have anticancer effects and reduce tumor growth in renal cell carcinoma in vitro and in vivo . However, it has been unclear whether SGLT2 inhibitors clinically exert anticancer effects in mRCC.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В немалом числе работ, опубликованных главным образом в 2016-2018 гг., представлены результаты изучения влияния ингибиторов SGLT2 (в первую очередь дапаглифлозина и канаглифлозина) в экспериментах in vitro, проводившихся на культивируемых линиях опухолевых клеток [18][19][20][21]. В частности, исследовались линии рака толстой кишки [18], почечно-клеточной карциномы [19], рака печени [20], а также бронхокарциномы и рака предстательной железы [21].…”
Section: экспериментальные исследования онкологической направленностиunclassified
“…В немалом числе работ, опубликованных главным образом в 2016-2018 гг., представлены результаты изучения влияния ингибиторов SGLT2 (в первую очередь дапаглифлозина и канаглифлозина) в экспериментах in vitro, проводившихся на культивируемых линиях опухолевых клеток [18][19][20][21]. В частности, исследовались линии рака толстой кишки [18], почечно-клеточной карциномы [19], рака печени [20], а также бронхокарциномы и рака предстательной железы [21]. Практически все эти исследования продемонстрировали ингибирование роста трансформированных клеток при добавлении в культуру упомянутых глифлозинов на основе, среди прочего, таких механизмов, как торможение клеточного цикла и усиление апоптоза [19], угнетение гликолиза, ангиогенеза [20], липогенеза и -подобно метформину -процессов клеточного дыхания, регулируемых митохондриальным комплексом I [21].…”
Section: экспериментальные исследования онкологической направленностиunclassified